The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.pcc.0000163979.33774.89
|View full text |Cite
|
Sign up to set email alerts
|

The strong ion gap predicts mortality in children following cardiopulmonary bypass surgery*

Abstract: An elevated strong ion gap occurs commonly following bypass surgery and appears to be superior to lactate as a mortality predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…40 41 However, Durward et al showed not only that the SIG was a common cause of metabolic acidosis after CPB, but that the SIG was superior to lactate as a predictor of mortality following open cardiac surgery. 29 While there may have been differences in case mix between that patient population and our own, it is interesting to note that hyperchloraemia was also associated with survival in that study. 29 Mortality in this study group was only 1%.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…40 41 However, Durward et al showed not only that the SIG was a common cause of metabolic acidosis after CPB, but that the SIG was superior to lactate as a predictor of mortality following open cardiac surgery. 29 While there may have been differences in case mix between that patient population and our own, it is interesting to note that hyperchloraemia was also associated with survival in that study. 29 Mortality in this study group was only 1%.…”
Section: Discussionmentioning
confidence: 61%
“…29 While there may have been differences in case mix between that patient population and our own, it is interesting to note that hyperchloraemia was also associated with survival in that study. 29 Mortality in this study group was only 1%. Patients were not pre-selected by diagnosis or surgical procedure at the time of enrolment and we believe the study group is representative of children undergoing open cardiac surgery at this institution, for whom overall mortality was comparable at 2.4%.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Conversely, several studies have suggested that a hyperchloraemic acidosis may carry a more favourable prognosis [27,28,31]. …”
Section: Discussionmentioning
confidence: 99%
“…In a large study of adult intensive care unit (ICU) patients, metabolic acidosis due to hyperlactataemia was the strongest predictor of mortality, compared with hypercholoraemic acidosis and non-lactate acidosis 37. In children, three studies (total n=453) found non-lactate acidosis to be superior to blood lactate in predicting mortality in acutely ill children in PICU,33 38 39 but other researchers found that it compared less favourably 27 37…”
Section: Indications and Limitationsmentioning
confidence: 99%